Oral manifestations in pediatric patients with nephritis lupus - Noriega, S (2017)
Objective: The aim of this study was describe the most frequent oral manifestations in patients with Nephritis Lupus (LN)  as well as to make an updated bibliographic review of the classification, clinical treatment, treatment and dental management of the disease. Materials and method: A cross-sectional study was carried out with 9 children suffering from LN between the ages of 1 and 18 years, from the Pediatric Nephrology Service of the Hospital City Dr. Enrique Tejera, in Valencia, Venezuela, during the year 2016. Results: The results showed: more frequency of LN in female patients, with prevalence of 15 years old, and histological more frequent type III of LN. The oral manifestations found were: cheilitis, white spots, discoid erythema, geographical language, painless oral ulcers, cold sores, gingival enlargement, gingivitis, dry  mouth, pallor of oral mucosa and glossitis. Conclusions: It is concluded that the patient with LN has oral manifestations related to the systemic disease that suffers.